Bounded Agility in Hybrid Organization: Bridging Fiscal Duties and Regulatory Constraints in Lembaga Manajemen Aset Negara - Reza Pranata Putra; Ria Ananda Putri; Muhammad Iqbal Maulana; Yola Rezki Handika (Smart Society, 2026)
The transformation of public organizations into hybrid entities has created increasing complexity in governance, particularly when administrative flexibility must coexist with strict fiscal compliance. In the Indonesian public sector context, the State Asset Management Agency (Lembaga Manajemen Aset Negara/LMAN), operating as a Public Service Agency (Badan Layanan Umum/BLU) while simultaneously registered as a Taxable Entrepreneur (Pengusaha Kena Pajak/PKP), faces unique institutional challenges in balancing its dual mandate of public service delivery and fiscal compliance. This study aims to analyze LMAN's institutional strategy in managing fiscal duty through an agile governance perspective. This study uses a descriptive qualitative approach, utilizing in-depth interviews with nine key informants from within and outside the organization, supported by observation and document analysis. Data were analyzed using an interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that agile governance in LMAN is not solely driven by structural transformation but emerges through flexible work processes, adaptive decision-making, and the active role of human resources in responding to the dynamics of change. Organizational agility is supported by cross-unit coordination and the use of technology as a supporting tool rather than a primary driver. This study identifies the concept of bounded agility, which is a form of organizational agility that operates within the constraints of institutional regulations and strict fiscal compliance. These findings highlight that agility in public organizations is process-driven and actor-centered, rather than structurally imposed. This study contributes to the literature by extending agile governance theory to the context of fiscal compliance in public organizations, offering a new perspective on how adaptive capacity is shaped under institutional regulation. Practically, this study provides insights for policymakers and implementers in designing more adaptive governance mechanisms for hybrid public organizations facing dual administrative and fiscal demands.